Management of Parkinson's Disease medication in acutely admitted patients. Issue 1 (24th October 2012) - Sathyababu, Renay; Chan, Edmund; Dhakam, Zahid
Abstract: This project aimed to identify problems in the management of Parkinson's Disease (PD) medications in those acutely admitted to the medical ward. Errors in prescription of medications are due to difficulties in conversion of formulation of medications to suit different needs, lack of awareness of help available amongst junior doctors and lack of awareness of trust guidance. Drug charts were audited over two weeks on medical wards. Dosing, frequency, formulation, and any difficulties in the administration were noted. A survey of junior doctors regarding their knowledge of PD management was also undertaken. The effects of our interventions (creation of summary guidance made available on wards, advice regarding where to obtain prescription information, and teaching sessions) were evaluated using a survey and audit. There was improved accuracy in PD prescriptions, improved confidence in switching formulation, increased awareness of trust guidance and the consequences of missed doses of PD medications. However there was no improvement in knowledge about appropriate resources used to make correct prescriptions. Increased education and training is required to continue improvement in prescription accuracy and awareness of where to seek help, to improve patient safety.